Language Assimilation among Chinese, Javanese, and Madurese in Jember: A Descriptive Analysis of Language in a Multicultural Community - Dwi Puspitarini (Fenomena, 2009)
The phenomenon of language assimilation in multicultural communities has become a crucial issue due to intensive interactions among ethnic groups with different linguistic and cultural backgrounds. This study employs a sociolinguistic framework to understand language use as an ethnic identity marker in social communication. The research aims to describe the languages used in social interactions among Chinese, Madurese, and Javanese ethnic groups at Pasar Tanjung Jember, and to analyze how these languages reflect ethnic identity and influence inter-ethnic intimacy. This descriptive qualitative research was conducted through observation, in-depth interviews, and field notes involving sellers and buyers on the first floor of Pasar Tanjung. The findings reveal four languages used: Javanese, Madurese, Indonesian, and Chinese (Mandarin), with varying usage depending on context and interlocutor. The Chinese ethnic group tends to use Indonesian in formal situations and Javanese ngoko in informal settings, while Chinese is reserved for intra-ethnic communication. It is concluded that language assimilation primarily occurs within the Chinese minority due to factors such as tolerance, economic necessity, and cultural sympathy, and further research on assimilation's impact on native language retention is recommended. Fenomena asimilasi bahasa dalam masyarakat multikultural menjadi isu krusial akibat interaksi intensif antar etnis yang berbeda latar belakang bahasa dan budaya. Penelitian ini menggunakan kerangka sosiolinguistik untuk memahami penggunaan bahasa sebagai penanda identitas etnis dalam komunikasi sosial. Tujuan penelitian adalah mendeskripsikan bahasa yang digunakan dalam interaksi sosial antara etnis Tionghoa, Madura, dan Jawa di Pasar Tanjung Jember, serta menganalisis bagaimana bahasa tersebut menunjukkan identitas etnis dan mempengaruhi keintiman hubungan antaretnis. Penelitian kualitatif deskriptif ini dilakukan melalui observasi, wawancara mendalam, dan pencatatan lapangan terhadap penjual dan pembeli di lantai satu Pasar Tanjung. Hasil penelitian menunjukkan bahwa terdapat empat bahasa yang digunakan: Bahasa Jawa, Bahasa Madura, Bahasa Indonesia, dan Bahasa Tionghoa (Mandarin), dengan tingkat penggunaan yang bervariasi tergantung situasi dan lawan tutur. Etnis Tionghoa cenderung menggunakan bahasa Indonesia dalam situasi formal dan bahasa Jawa ngoko dalam situasi informal, sementara Bahasa Tionghoa hanya digunakan sesama etnis Tionghoa. Disimpulkan bahwa asimilasi bahasa terjadi terutama pada kelompok minoritas Tionghoa karena faktor toleransi, ekonomi, dan simpati budaya, dan direkomendasikan adanya penelitian lebih lanjut tentang dampak asimilasi terhadap retensi bahasa ibu.